ANALISIS PENGARUH LABA AKUNTANSI, ARUS KAS BEBAS, DAN HARGA SAHAM TERHADAP DIVIDEN KAS (Studi pada Perusahaan Manufaktur Subsektor Makanan dan Minuman yang Tercatat di BEI Periode 2010-2014) - Trias Anggundini; Khairunnisa Khairunnisa; Muhamad Muslih (Jurusan Akuntansi Politeknik Negeri Bandung, 2016)
Abstract: The purpose of this research is to find out the effect of accounting profit, free cash flow, and stock prices on cash dividend measured by dividend per share, either simultaneously or partially. This research is descriptive verification and causality research. Unit analysis that used in this research is manufacturing food and beverage subsector. This research using sampel data which chosen through purposive sampling technique and there are 7 firms during five years, from 2010-`2014. Ths research using panel data regression analysis technique. The results show that simultaneously, accounting profit, free cash flow, and stock prices have effect on cash dividend. Partially, profit accounting and free cash flow have no effect on cash dividend. Meanwhile, stock price has positive effect on cash dividend Keyword: Accounting Profit, Free Cash Flow, Stock Price, Cash Dividend, Dividend per Share